2020
DOI: 10.3892/ijmm.2020.4528
|View full text |Cite
|
Sign up to set email alerts
|

AMPK activation protects astrocytes from hypoxia‑induced cell death

Abstract: Adenosine monophosphate (AMP)-activated protein kinase (AMPK) is a major cellular energy sensor that is activated by an increase in the AMP/adenosine triphosphate (ATP) ratio. This causes the initiation of adaptive cellular programs, leading to the inhibition of anabolic pathways and increasing ATP synthesis. AMPK indirectly inhibits mammalian target of rapamycin (mTOR) complex 1 (mTORc1), a serine/threonine kinase and central regulator of cell growth and metabolism, which integrates various growth inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…However, the specific binding molecules and their sites of binding to TIMP3 to modify the phosphorylation of AKT in I/R injury were unknown, which will be investigated further in the future. It has been previously demonstrated that the AKT pathway is activated in hypoxia-induced neuronal injury, which is contrary to the findings of the present study (28). These inconsistent results may be caused by the different models applied.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the specific binding molecules and their sites of binding to TIMP3 to modify the phosphorylation of AKT in I/R injury were unknown, which will be investigated further in the future. It has been previously demonstrated that the AKT pathway is activated in hypoxia-induced neuronal injury, which is contrary to the findings of the present study (28). These inconsistent results may be caused by the different models applied.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, tumour cells are more susceptible to the treatment with glycolysis inhibitors like 2-DG 50 . In consequence of glycolysis inhibition, ATP is depleted and AMPK is activated 8,51 . Our results demonstrate that AMPK DKO cells show an impaired adaptation to energy starvation conditions and thus it seems plausible that these cells are more sensitive to glycolysis inhibition than wildtype cells.…”
Section: Discussionmentioning
confidence: 99%
“…We used an in vitro hypoxia model to simulate cardiac ischemia. Mouse cardiomyocyte cells (HL-1) cultured in BD GasPak Pouches (BD Biosciences, Cockeysville, MD, USA) were subjected to hypoxia (0.1% oxygen) for 16 h [ 25 ]. HL-1 cell apoptosis was detected using the DeadEnd™ Colorimetric TUNEL System.…”
Section: Methodsmentioning
confidence: 99%